Likely damaging de novo variants in congenital diaphragmatic hernia patients are associated with worse clinical outcomes. - Qiao, Lu; Wynn, Julia; Yu, Lan; Hernan, Rebecca; Zhou, Xueya; Duron, Vincent; Aspelund, Gudrun; Farkouh-Karoleski, Christiana; Zygumunt, Annette; Krishnan, Usha S; Nees, Shannon; Khlevner, Julie; et al. (Genet Med, 2020)
PURPOSE: Congenital diaphragmatic hernia (CDH) is associated with significant mortality and long-term morbidity in some but not all individuals. We hypothesize monogenic factors that cause CDH are likely to have pleiotropic effects and be associated with worse clinical outcomes. METHODS: We enrolled and prospectively followed 647 newborns with CDH and performed genomic sequencing on 462 trios to identify de novo variants. We grouped cases into those with and without likely damaging (LD) variants and systematically assessed CDH clinical outcomes between the genetic groups. RESULTS: Complex cases with additional congenital anomalies had higher mortality than isolated cases (P = 8 × 10). Isolated cases with LD variants had similar mortality to complex cases and much higher mortality than isolated cases without LD (P = 3 × 10). The trend was similar with pulmonary hypertension at 1 month. Cases with LD variants had an estimated 12-17 points lower scores on neurodevelopmental assessments at 2 years compared with cases without LD variants, and this difference is similar in isolated and complex cases. CONCLUSION: We found that the LD genetic variants are associated with higher mortality, worse pulmonary hypertension, and worse neurodevelopment outcomes compared with non-LD variants. Our results have important implications for prognosis, potential intervention and long-term follow up for children with CDH.
Keywords: Child; Hernias, Diaphragmatic, Congenital; Humans; Infant, Newborn; Retrospective Studies

De novo variants in congenital diaphragmatic hernia identify MYRF as a new syndrome and reveal genetic overlaps with other developmental disorders. - Qi, Hongjian; Yu, Lan; Zhou, Xueya; Wynn, Julia; Zhao, Haoquan; Guo, Yicheng; Zhu, Na; Kitaygorodsky, Alexander; Hernan, Rebecca; Aspelund, Gudrun; Lim, Foong-Yen; Crombleholme, Timothy; et al. (PLoS Genet, 2018)
Congenital diaphragmatic hernia (CDH) is a severe birth defect that is often accompanied by other congenital anomalies. Previous exome sequencing studies for CDH have supported a role of de novo damaging variants but did not identify any recurrently mutated genes. To investigate further the genetics of CDH, we analyzed de novo coding variants in 362 proband-parent trios including 271 new trios reported in this study. We identified four unrelated individuals with damaging de novo variants in MYRF (P = 5.3x10(-8)), including one likely gene-disrupting (LGD) and three deleterious missense (D-mis) variants. Eight additional individuals with de novo LGD or missense variants were identified from our other genetic studies or from the literature. Common phenotypes of MYRF de novo variant carriers include CDH, congenital heart disease and genitourinary abnormalities, suggesting that it represents a novel syndrome. MYRF is a membrane associated transcriptional factor highly expressed in developing diaphragm and is depleted of LGD variants in the general population. All de novo missense variants aggregated in two functional protein domains. Analyzing the transcriptome of patient-derived diaphragm fibroblast cells suggest that disease associated variants abolish the transcription factor activity. Furthermore, we showed that the remaining genes with damaging variants in CDH significantly overlap with genes implicated in other developmental disorders. Gene expression patterns and patient phenotypes support pleiotropic effects of damaging variants in these genes on CDH and other developmental disorders. Finally, functional enrichment analysis implicates the disruption of regulation of gene expression, kinase activities, intra-cellular signaling, and cytoskeleton organization as pathogenic mechanisms in CDH.
Keywords: Child, Preschool; Developmental Disabilities; DNA Copy Number Variations; Female; Genetic Variation; Heart Defects, Congenital; Hernias, Diaphragmatic, Congenital; Humans; Infant, Newborn; Longitudinal Studies; Male; Membrane Proteins; Mutation; Mutation, Missense; Phenotype; Sequence Analysis, RNA; Syndrome; Transcription Factors; Whole Exome Sequencing; Whole Genome Sequencing